2015
DOI: 10.1038/nrendo.2014.236
|View full text |Cite
|
Sign up to set email alerts
|

Thinking bedside at the bench: the NOD mouse model of T1DM

Abstract: Studies over the past 35 years in the nonobese diabetic (NOD) mouse have shown that a number of agents can prevent or even reverse type 1 diabetes mellitus (T1DM); however, these successes have not been replicated in human clinical trials. Although some of these interventions have delayed disease onset or progression in subsets of participants, none have resulted in a complete cure. Even in the most robust responders, the treatments do not permanently preserve insulin secretion or stimulate the proliferation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
95
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(95 citation statements)
references
References 103 publications
0
95
0
Order By: Relevance
“…There are numerous examples of successful interventions in NOD mice that have failed in humans including anti-CD3 therapy and oral insulin. These are eloquently reviewed by Reed and Herold [23]. There are a variety of reasons of why the pre-clinical studies in NOD mice may not lead to success in clinical trials.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…There are numerous examples of successful interventions in NOD mice that have failed in humans including anti-CD3 therapy and oral insulin. These are eloquently reviewed by Reed and Herold [23]. There are a variety of reasons of why the pre-clinical studies in NOD mice may not lead to success in clinical trials.…”
mentioning
confidence: 97%
“…Indeed intervention in NOD mice is usually made early and it has been shown that early intervention is most likely to successfully prevent Type 1 diabetes development in this model. Other problems include immunological differences between mice and humans and dosing issues [23]. It should also be noted that incidence of diabetes in NOD mice increases in a clean (specific pathogen free) environment [24] whereas in humans environmental factors such as viruses may play an important aspect of disease development [25].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…But this approach may fall short in terms of reflecting critical aspects of human islet pathophysiology [15,16]. Because islets of non-human primate (NHP) or human origin are increasingly becoming available (albeit in limited numbers), there is an important and creeping increase in the number of studies on primate islets.…”
Section: Introductionmentioning
confidence: 99%
“…Mice in particular are a common model in hypothesis-driven cardiovascular research (Treuting et al, 2012) due to their short lifespan, their small size, the similarity of their well-decrypted genome with the human one and, most importantly, the possibility to induce genetic modifications (Pennacchio, 2003). Genetically or pharmacologically altered mouse models have provided insight into (amongst many other cardiovascular applications) abdominal aortic aneurysm (Trachet et al, 2014a,b), stable and unstable atherosclerotic plaque (Van der Donckt et al, 2014;De Wilde et al, 2015), diabetes (Reed and Herold, 2015), hypertrophy (Yamaguchi et al, 2007) and Marfan syndrome (Campens et al, 2015). However, since mice have a much smaller (aortic dimensions are 10x smaller, Tab.…”
Section: Introductionmentioning
confidence: 99%